Screening Discrimination in Financial Markets: Evidence from CEO-Fund Manager Dyads - Stefan Jaspersen; Peter Limbach (University of Cologne, Centre for Financial Research (CFR), 2020)
This study provides evidence that investors' demographic similarity to CEOs facilitates informed trading after accounting for selective distribution of information. Mutual fund managers overweight firms whose CEOs resemble them in terms of age, ethnicity, and gender. Significantly higher trade performance in the sub-portfolio of similar CEOs indicates that this overweighting reflects informational advantage. Consistently, for similar CEOs, fund managers are better able to identify valuable CEO-firm matches and firms with positive future earnings. The evidence supports theories of screening discrimination according to which in-group bias is a rational response to asymmetric information and has implications for fund manager diversity.
Keywords: G11; G23; J10; 330; CEO-investor demographic similarity; fund manager diversity; in-group bias; informational advantage; investment decisions; mutual fund performance; screening discrimination